The Impact of The Economic Factor on The Country's Foreign Policy - Ahmed Babakr Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The foreign policy of any country expresses its status, its economic and military policies, and the real state of the country itself. There are also several factors that have their implications on the foreign policies of international units, and this research highlights the economic factor as the most important factor for the foreign policies of countries, and that the role of the economy is shown in terms of positive and negative aspects in the foreign policies of countries, and shows the importance of this research that the foreign policies for any country, it expresses the status and prestige of the country itself.